A Pengembangan Instrumen Self Efficacy-Academic di SMK Negeri 1 Tengaran: Pengembangan Instrumen Self Efficacy-Academic di SMK Negeri 1 Tengaran - Purwanti Purwanti (Universitas Muhammadiyah Kotabumi, 2023)
Abstract: This study aims to develop and validate an assessment instrument on Academic Self Efficacy as a measurement of self-efficacy in the context of education in Indonesia. This instrument is designed based on self-efficacy theory and a literature review related to self-efficacy measurement. This research uses a Development Research (R&D) design. The development model used is the Borg &Gall model with five stages of development, namely research, information collecting, planning, developing a preliminary product, preliminary field testing, and main product revision. The subjects of the study were 2 expert lecturers and 105 students from class XI Software Engineering Expertise Competencies and Culinary Expertise Competencies of SMK Negeri 1 Tengaran. The validity of inventory items is calculated using the Pearson Product Moment correlation formula processed with the IBM SPSS Statistics 22 application and reliability analysis with the Cronbach Alpha formula. The results showed that: the self-efficacy instrument in the form of Inventory consists of 45 statements declared valid with a CVR value greater than 0.99, a Product Moment value (r calculated) greater than 0.195 (r table), and reliable with a reliability value of 0.926. Keywords: Intrument, Self Efficacy Academic. Abstrak: Penelitian ini bertujuan untuk untuk mengembangkan dan memvalidasi instrumen assessment tentang Self Efficacy Academic sebagai alat ukur self-efficacy di konteks pendidikan di Indonesia. Instrumen ini dirancang berdasarkan teori self-efficacy dan review literatur terkait pengukuran self-efficacy. Penelitian ini menggunakan rancangan Penelitian Pengembangan (R&D). Model pengembangan yang digunakan adalah model Borg &Gall dengan lima tahapan pengembangan yaitu research and information collecting, planning, develop preliminary of product, preliminary field testing dan main product revision. Subjek penelitian adalah 2 orang dosen ahli dan 105 peserta didik dari kelas XI Kompetensi Keahlian Rekayasa Perangkat Lunak dan Kompetensi Keahlian Kuliner SMK Negeri 1 Tengaran. Analisis yang digunakan adalah Validitas item inventory dihitung menggunakan rumus korelasi Pearson Product Moment yang diolah dengan aplikasi IBM SPSS Statistics 22 dan analisis reliabilitas dengan formula Alpha Cronbach. Hasil penelitian menunjukkan bahwa : instrumen self-efficacy berupa Inventory terdiri dari 45 butir pernyataan dinyatakan valid dengan nilai CVR lebih besar dari 0,99, serta nilai Product Moment (r hitung) lebih besar dari 0,195 (r tabel), dan reliabel dengan nilai reliabilitas 0,926. Kata Kunci: Intrumen, Self Efficacy Academic